2002
DOI: 10.1292/jvms.64.813
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and Function of Murine Peritoneal Cavity Macrophage Derived-Dendritic Cells.

Abstract: ABSTRACT. The accessory activity was reported in murine peritoneal cavity macrophage derived dendritic cells (PEC-DC) in a mixed lymphocyte reaction (MLR). Here we continue the characterization of the generated PEC-DC using the criteria of morphology, phenotype and other accessory function. We have demonstrated that murine peritoneal cavity macrophages can be induced to differentiate in vitro into cells exhibiting typical dendritic cell (DC) morphology, phenotype and function. The proliferative capacity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Great progress has been achieved in the last decade by several groups that have succeeded in the establishment of procedures for the in vitro generation of murine and human DC from progenitors in the bone marrow, placental and umbilical cord blood, and cytokine mobilized peripheral blood [16, 38, 51, 52,79,80,91,126,151,155,156,180]. Methods have also been developed to generate DC from blood monocytes [8,112,117,119,121] and murine peritoneal cavity macrophages [88]. Long-term DC lines have also recently been generated from fetal tissues using either granulocyte macrophage colony stimulating factor (GM-CSF) [173] or stromal cell culture supernatants [157].…”
Section: Dendritic Cell Ontogenymentioning
confidence: 99%
See 1 more Smart Citation
“…Great progress has been achieved in the last decade by several groups that have succeeded in the establishment of procedures for the in vitro generation of murine and human DC from progenitors in the bone marrow, placental and umbilical cord blood, and cytokine mobilized peripheral blood [16, 38, 51, 52,79,80,91,126,151,155,156,180]. Methods have also been developed to generate DC from blood monocytes [8,112,117,119,121] and murine peritoneal cavity macrophages [88]. Long-term DC lines have also recently been generated from fetal tissues using either granulocyte macrophage colony stimulating factor (GM-CSF) [173] or stromal cell culture supernatants [157].…”
Section: Dendritic Cell Ontogenymentioning
confidence: 99%
“…In our previous work we have demonstrated the effectiveness of metrizamide gradients [86,87,89]. Recent studies have shown great progress in the establishment of several procedures for the in vitro generation of DC from progenitors in the bone marrow, placental and umbilical cord blood [16,19,38,51,52,79,80,91,126,151,155,156,180]; monocytes [117,119] and peritonealcavity macrophages [88]. This is likely to be the right way forward, since many experimental protocols devised to study the in vivo stimulatory potential and the molecular mechanisms involved in antigen processing of DC require large numbers of DC, approximately (10 8 -10 9 ).…”
Section: Dendritic Cell Featuresmentioning
confidence: 99%
“…In parallel studies [22][23][24][25][26] have shown that Mø can differentiate into functional DC. Exposure to macrophage colony-stimulating factor (M-CSF) induces only macrophage formation, whereas granulocyte-macrophage colony-stimulating factor (GM-CSF) also induces DC formation [28,49].…”
mentioning
confidence: 99%
“…PP comprise transmucosal clusters of lymphoid follicles in the small intestine. In rats, PP are usually 3-4 mm long [14,18,26] but in large animals, for example cattle, PP may extend up to 4 m along the intestine [9]. Studies in pig, sheep, cattle have shown that there are two separate types of PP, which are morphologically different: discrete Peyer's Patches (DPP) scattered throughout the jejunum and a large continuous patch in the terminal ileum [9,20,27,38].…”
mentioning
confidence: 99%
See 1 more Smart Citation